1997
DOI: 10.1128/mcb.17.3.1160
|View full text |Cite
|
Sign up to set email alerts
|

Cdc73p and Paf1p Are Found in a Novel RNA Polymerase II-Containing Complex Distinct from the Srbp-Containing Holoenzyme

Abstract: The products of the yeast CDC73 and PAF1 genes were originally identified as RNA polymerase II-associated proteins. Paf1p is a nuclear protein important for cell growth and transcriptional regulation of a subset of yeast genes. In this study we demonstrate that the product of CDC73 is a nuclear protein that interacts directly with purified RNA polymerase II in vitro. Deletion of CDC73 confers a temperature-sensitive phenotype. Combination of the cdc73 mutation with the more severe paf1 mutation does not result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
183
3
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(197 citation statements)
references
References 62 publications
10
183
3
1
Order By: Relevance
“…The slm3D mutation is known to be synthetically lethal with the cdc73D mutation (Tong et al 2004). CDC73 encodes a constituent of the Paf1 complex with RNA polymerase II (Shi et al 1997;Krogan et al 2003). Interestingly, the cdc73D mutant was also unable to grow under high pressure and low temperature (see below).…”
Section: Resultsmentioning
confidence: 99%
“…The slm3D mutation is known to be synthetically lethal with the cdc73D mutation (Tong et al 2004). CDC73 encodes a constituent of the Paf1 complex with RNA polymerase II (Shi et al 1997;Krogan et al 2003). Interestingly, the cdc73D mutant was also unable to grow under high pressure and low temperature (see below).…”
Section: Resultsmentioning
confidence: 99%
“…2A-C). The latter fragment of parafibromin contains the region from residues 233 to 525 homologous to cdc73p, the yeast RNA polymerase II accessory factor component of the Paf1 complex (20,21). Because yeast cdc73p and the other yeast Paf1 complex components are nuclear proteins (22), and because human parafibromin (hCdc73) has been identified as a component of a human PAF1 complex (12)(13)(14), it was expected that GFP-HRPT2-C would exhibit nuclear localization like the full-length parafibromin fusion (GFP-HRPT2-A).…”
Section: Resultsmentioning
confidence: 99%
“…A description of the role of FCP1 in the CTD phosphorylation cycle is provided below. Further experimentation identified that TFIIF associates with multiple elongation factors, including the Spt5 subunit of DSIF , and components of the PAF complex (Shi et al 1997). TFIIF also appears to influence the TFIIS cleavage factor (see below) (Elmendorf et al 2001;Zhang et al 2003a).…”
Section: Tfiifmentioning
confidence: 99%
“…Paf1 is found in a complex with four additional subunits, Ctr9, Cdc73, Rtf1, and Leo1 (Shi et al 1996(Shi et al , 1997Krogan et al 2002b;Mueller and Jaehning 2002;Squazzo et al 2002). Genetic studies of PAF subunits revealed a wide range of phenotypes, including transcript elongation phenotypes (Costa and Arndt 2000;Mueller and Jaehning 2002;Squazzo et al 2002;Mueller et al 2004).…”
Section: Paf Complexmentioning
confidence: 99%